Determinants of iron accumulation in deep grey matter of multiple sclerosis patients. (November 2014) - Ropele, Stefan; Kilsdonk, Iris D; Wattjes, Mike P; Langkammer, Christian; de Graaf, Wolter L; Frederiksen, Jette L; Larsson, Henrik B; Yiannakas, Marios; Wheeler-Kingshott, Claudia AM; Enzinger, Christian; Khalil, Michael; Rocca, Maria A; et al.
Background: Iron accumulation in deep grey matter (GM) structures is a consistent finding in multiple sclerosis (MS) patients. This study focused on the identification of independent determinants of iron accumulation using R2 * mapping. Subjects and methods: Ninety-seven MS patients and 81 healthy controls were included in this multicentre study. R2 * mapping was performed on 3T MRI systems. R2 *in deep GM was corrected for age and was related to disease duration, disability, T2 lesion load and brain volume. Results: Compared to controls, R2 * was increased in all deep GM regions of MS patients except the globus pallidus and the substantia nigra. R2 * increase was most pronounced in the progressive stage of the disease and independently predicted by disease duration and disability. Reduced cortical volume was not associated with iron accumulation in the deep GM with the exception of the substantia nigra and the red nucleus. In lesions, R2 * was inversely correlated with disease duration and higher total lesion load. Conclusion: Iron accumulation in deep GM of MS patients is most strongly and independently associated with duration and severity of the disease. Additional associations between cortical GM atrophy and deep GM iron accumulation appear to exist in a region specific manner.